MENELUSURI KEINDAHAN BUDAYA NGAROT DI INDRAMAYU: JEJAK TRADASI DAN KEARIFAN LOKAL - Isad Suhaeb; Eva Farhah (UHN IGB Sugriwa Denpasar, 2024)
This study explores the beauty of Ngarot culture in Indramayu, a tradition rich in local heritage and traditional wisdom. Ngarot is a ceremony that is related to agricultural issues. This ceremony is found in Lelea Village, Lelea District, Indramayu Regency. The ngarot ceremony is participated in by the younger generation and continues from year to year without interruption. Ngarot is essentially an artistic entertainment festival for the younger generation that is enhanced with various types of traditional arts, apart from that, Ngarot is also an effort for the younger generation to increase their devotion to God Almighty, improve their character, work, participate in development, collaborate, synergize, respect each other, strengthening solidarity and regional security. This research uses a qualitative approach, investigating traces of tradition and their cultural and economic implications in the tourism context. This research method involves interviews, participant observation, and content analysis. Aims to further explore and document this rich cultural heritage and local wisdom contained in the Ngarot tradition. Through this activity, it is hoped that we can strengthen understanding of unique cultural values ​​and their contribution to local identity and economic sustainability of communities in Indramayu. The results reveal that the Ngarot traditional ceremonial tradition is not only a tourist attraction, but also an important symbol of local identity and a source of community economic sustainability. This research provides an in-depth understanding of how cultural heritage and local wisdom can become the main attraction in sustainable tourism development. Keywoards: Ngarot, Cultur, Tourism, local wisdom